Frequency measurements of CD3OH and (CH3OH)-C-13 optically pumped far-infrared laser lines - Bertolini, A.; Carelli, G.; Moraes, João Carlos Silos [UNESP]; Moretti, A.; Strumia, F.; Telles, E. M.; Scalabrin, A.; Pereira, D. (Optical Soc Amer, 1997)
We report the frequency measurements of 18 optically pumped far-infrared (FIR) laser lines generated from CD3OH and (CH3OH)-C-13. We use the heterodyne technique of mixing FIR laser radiations and microwave radiation on a metal-insulator-metal point-contact tunnel diode to determine the FIR laser frequencies. Two FIR laser systems, consisting of CO2 waveguide pump lasers and Fabry-Perot FIR laser cavities, were used as optical sources. (C) 1997 Optical Society of America.